Odpowiedź :
Odpowiedź:
(3/5 - 1/3) : (1 + 1/3) = (9/15 - 5/15) : 1 i 1/3 = 4/15 : 1 i 1/3 = 4/15 * 3/4 = 1/5
15 * 3 i 2/5 = 15 * 17/5 = 51
3 i 3/5 * 1 i 2/3 = 18/5 * 5/3 = 6
5 i 2/5 : 4 i 1/2 = 27/5 : 9/2 = 27/5 * 2/9 = 6/5 = 1 i 1/5
Odpowiedź:
a) (3/5 - 1/3) : (1+1/3) = (9/15 - 5/15) : (3/3 + 1/3) = 4/15 : 4/3 = 4/15 * 3/4 = 1/5
b) 15 * 3 2/5 = 15/1 * 17/5 = 51
c) 3 3/5 * 1 2/3 = 18/5 * 5/3 = 6
d) 5 2/5 : 4 1/2 = 27/5 : 9/2 = 27/5 * 2/9 = 6/5 = 1 1/5
Mam nadzieję, że dobrze i że w pośpiechu nigdzie się nie pomyliłam. Z góry przepraszam, jeśli tak było. Pozdrawiam.